STUDYING THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE WITH ORGANIZATIONAL COMMITMENT AT MINHAJ SHAHABAH ISLAMIC BOARDING SCHOOL BOGOR - Pratama, Haris Rizky; Sunaryo, Widodo; Yusnita, Nancy (UNIVERSITAS PAKUAN, 2020)
This study aims to determine the Correlation between Transformational Leadership and Organizational Culture with Organizational Commitment at Minhaj Shahabah Islamic Boarding School Bogor. This study was conducted at Pesantren Minhaj Shahabah Bogor in 2020 and it used survey method with the correlation approach. This study population was 146 employees and the number of sample was 107 employees by proportionate random sampling technique. The collected research data will be analysed by descriptive statistics and inferential statistics. Inferential statistics is used for testing the hypotheses using regression analysis technique, simple correlation and multiple correlation. The results show that 1) there is a positive highly significant correlation berween transformational leadership with organizational commitment with coefficient of correlation (ry.1) is 0,989, coefficient of determination (ry.1)² is 0,978, and supported by regression equation of Å¶ = 14,150 + 0,853 X1, 2) there is a is a positive highly significant correlation between organizational culture with organizational commitment, with coefficient of correlation (ry.2) is 0,993, coefficient of determination (ry.2)² is 0,986, and supported by regression equation Å¶ = 5,992 + 0,932 X2, and 3) there is a positive highly significant correlation between transformational leadership and organizational culture and organizational commitment with coefficient of correlation (ry.1.2) is 0,994 and coefficient of determination (ry.1.2)² is 0,988 and supported by regression equation Å¶ = 7,698 + 0,260X1 + 0,651X2. Therefore, it can be concluded that organizational commitment can be enhanced through transformational leadership and organizational culture.